'Building on shaky ground'—challenges to and solutions for primary care guideline implementation in four provinces in South Africa: a qualitative study. Issue 5 (30th May 2020) - Kredo, Tamara; Cooper, Sara; Abrams, Amber Louise; Muller, Jocelyn; Schmidt, Bey-Marrié; Volmink, Jimmy; Atkins, Salla
Abstract : Objectives: Clinical guidelines support evidence-informed quality patient care. Our study explored perspectives of South African subnational health managers regarding barriers to and enablers for implementation for all available primary care guidelines. Design: We used qualitative research methods, including semistructured, individual interviews and an interpretative perspective. Thematic content analysis was used to develop data categories and themes. Setting: We conducted research in four of nine South African provinces with diverse geographic, economic and health system arrangements (Eastern Cape, Western Cape, KwaZulu-Natal, Limpopo). South Africa is a middle-income country with high levels of inequality. The settings represented public sector rural and peri-urban health facilities. Participants: Twenty-two participants with provincial and district health management roles, that comprised implementation and/or training on primary care guidelines, were included. Results: Participants recommended urgent consideration of health system challenges, particularly financial constraints, impacting on access to the guidelines themselves and to medical equipment and supplies necessary to adhere to guidelines. They suggested that overcoming service delivery gaps requires strengthening of leadership, clarification of roles and enhanced accountability. Participants suggested that inadequate numbers of skilled clinical staff hampered guideline use and, ultimately, patient care. Quality assurance of training programmes for clinicians—particularly nurses—interdisciplinary training, and strengthening post-training mentorship were recommended. Furthermore, fit-for-purpose guideline implementation necessitates considering the unique settings of facilities, including local culture and geography. This requires guideline development to include guideline end users. Conclusions: Guidelines are one of the policy tools to achieve evidence-informed, cost-effective and universal healthcare. But, if not effectively implemented, they have no impact. Subnational health managers in poorly resourced settings suggested that shortcomings in the health system, along with poor consultation with end users, affect implementation. Short-term improvements are possible through increasing access to and training on guidelines. However, health system strengthening and recognition of socio-cultural–geographic diversity are prerequisites for context-appropriate evidence-informed practice.